Zimra service procurement decision support system - Zimusi, Abel (Midlands State University, 2018)
This research is aimed at development of a Service Procurement Decision Support System that is meant to assist the ICT department in procurement decision making processes. The researcher had proposed the idea of introducing a new system after discovering problems that were being experienced as a result of manual processes, some of the problems include; delays in procurement decision making, corruption as some procurement members can choose their relatives or friends and also lack of consistency in procurement decision making. To identify these problems the researcher had used various data finding methodologies which includes questionnaires, interviews and observations. After discovery of the weaknesses of the system which was in place the researcher then came up with a solution in form of an automated procurement decision support system. The system allows the procurement section to quickly come up with a procurement decision without holding any meeting as the system give the decision makers the capabilities to login into the system and access the decision that would have been automatically generated by the system basing on the data that would have been captured for the service providers. Unified Modelling Language was used to carry out the in-depth analysis and also the design of the system. Objectives that had been stated were used as the guideline to the development of the project. These objectives were altered a bit due to the changing requirements of the system users and also the equipment available. The system can also be improved based on the system modules that needs to be changed and also to be in line with technological advancements.